2022
DOI: 10.1155/2022/5164265
|View full text |Cite
|
Sign up to set email alerts
|

Multidimension Analysis of the Prognostic Value, Immune Regulatory Function, and ceRNA Network of LY6E in Individuals with Colorectal Cancer

Abstract: Background. Lymphocyte antigen 6 complex, locus E (LY6E) is abnormally expressed in several cancers and is associated with poor outcomes. However, the biological role of LY6E in colorectal cancer (CRC) remains largely unknown. Hence, we aimed to evaluate the expression levels, prognostic value, biological functions, and immune effects of LY6E via pan-cancer and CRC analyses using multiple databases. Methods. We analyzed the expression pattern of LY6E in various cancers. The prognostic value of LY6E expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Regulates the T-cell receptor (TCR) signaling by interacting with component CD3Z/CD247 at the plasma membrane, leading to CD3Z/CD247 phosphorylation modulation (By similarity). It was shown that upregulation of LY6E expression was associated with poor prognosis in several cancers (Li et al, 2022, AlHossiny et al, 2016, and abnormal overexpression of LY6E was found to increase the expression of the HIF-1α gene mainly at the transcriptional level in mouse models. This promotes the expression of angiogenic factors VEGFA and PDGFB, leading to an increase in tumor vascular density, and targeting this pathway for cancer therapy is effective (Yeom et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Regulates the T-cell receptor (TCR) signaling by interacting with component CD3Z/CD247 at the plasma membrane, leading to CD3Z/CD247 phosphorylation modulation (By similarity). It was shown that upregulation of LY6E expression was associated with poor prognosis in several cancers (Li et al, 2022, AlHossiny et al, 2016, and abnormal overexpression of LY6E was found to increase the expression of the HIF-1α gene mainly at the transcriptional level in mouse models. This promotes the expression of angiogenic factors VEGFA and PDGFB, leading to an increase in tumor vascular density, and targeting this pathway for cancer therapy is effective (Yeom et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Regulates the T-cell receptor (TCR) signaling by interacting with component CD3Z/CD247 at the plasma membrane, leading to CD3Z/CD247 phosphorylation modulation (By similarity). It was shown that upregulation of LY6E expression was associated with poor prognosis in several cancers [ 14 16 ], and abnormal overexpression of LY6E was found to increase the expression of the HIF-1α gene mainly at the transcriptional level in mouse models. This promotes the expression of angiogenic factors VEGFA and PDGFB, leading to an increase in tumor vascular density, and targeting this pathway for cancer therapy is effective [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among other cancers, BATF2 was demonstrated as a tumor suppressor of gastric cancer [ 28 ], glioblastoma [ 29 ], and esophageal squamous cell carcinoma [ 30 ]. In contrast, LY6E , the other gene found as upregulated in ASD blood samples, was suggested as a biomarker of poor prognosis in smoking-induced lung carcinogenesis [ 31 ] and colorectal cancer [ 32 ]. Notably, several conjugates of anti-LY6E antibodies were proposed as solid tumor therapeutics [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%